(untitled) (International Journal of Physiotherapy, 2016)
Background: PFPS commonly leads to anterior or retro patellar knee pain. The etiology of PFPS is multi-factorial and various studies have identified abnormal patellar tracking, patellar malalignment, abnormal subtalar motion, decrease in navicular angle as some of the possible factors which might lead to PFPS. This comparative study investigates the lower extremity alignment during stance phase of gait cycle in subjects with and without patellafemoral pain syndrome. Methods: In this experimental study 14 male subjects suffering from PFPS were taken into Group A and 20 asymptomatic male subjects were taken into Group B. Video analysis of both groups were done in anterior, posterior and sagittal view. Still frames of initial contact, mid stance and terminal stance phases of the gait cycle and five angles i.e. standing foot angle, navicular angle, Q angle, A angle and rear foot angle for each of three phases were measured with image tool software. Results: The mean data showed that the standing foot angle, navicular angle, Q angle, A angle were increased in asymptomatic group when compared to the PFPS group in initial contact, mid stance and terminal stance but these increase in angles were not statistically significant. However the increase in rear foot angle in terminal stance of normal subjects compared to PFPS group was statistically significant (p value= 0.047) Conclusion: There exists an association of lower extremity angles with PFPS. Significant difference exists with respect to rear foot angle between PFPS and asymptomatic individuals. Rear foot angle decreases during the terminal stance in the PFPS subjects when compared to asymptomatic subjects